Predictors of Adolescent Pregnancy in Northeast India: A Cross-Sectional Analysis - Dipankar Roy; Avijit Debnath; Niranjan Roy; Munmi Sarma; Shanku Paul; Dipanjan Roy; Jayashree Das (National Journal of Community Medicine)
Background: Worldwide teenage pregnancy marks a major public health concern that hits hardest in countries with lower and medium incomes. A recent national family health survey study shows adolescent pregnancy rates climbed in three northeastern states while other parts of the country recorded progress. Understanding the factors contributing to marital teenage pregnancy is crucial for improving the health status of both mother and new born.